Interrater reliability of Western University's on-road assessment: Fiabilité interévaluateurs de l'examen pratique de conduite de la Western University. (December 2016) - Classen, Sherrilene; Krasniuk, Sarah; Knott, Melissa; Alvarez, Liliana; Monahan, Miriam; Morrow, Sarah; Danter, Tim
Background: Little empirical support exists for interrater reliability between evaluators from different backgrounds when assessing on-road outcomes of drivers. Purpose: We quantified interrater reliability of on-road outcomes between a certified driving school instructor (DI) and an occupational therapist and certified driver rehabilitation specialist (CDRS). Method: Both raters used the Global Rating Score (GRS) with two levels (pass, fail), the GRS with four levels (pass, pass with recommendations, fail remediable, fail), and the priority error rating score (PERS; most frequently occurring on-road errors in priority order) to assess 35 drivers (age, M = 48.31 years, SD = 9.76 years; 40% male; 86% with multiple sclerosis). Findings: The DI and occupational therapist CDRS had excellent agreement on the GRS with two levels (κ = .892, p < .0001), GRS with four levels (κ = .952, p < .0001), and the PERS (κ = .847–.902, p < .0001), indicating interrater reliability. Implications: This research contributes to empirical support for the on-road assessment.